2004
DOI: 10.1097/00006216-200401000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Patient Care Management as a Global Nursing Concern

Abstract: Effective and efficient patient management is important in all health care environments because it influences clinical and financial outcomes as well as capacity. Design of care management processes is guided by specific principles. Roles (e.g., case management) and tools (e.g., clinical paths) provide essential foundations while attention to outcomes anchors the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…(CMSA, 2005) The full immersion model of care management was built from concepts found in the case management literature related to role functions of discharge planning, utilization review, and care coordination or facilitation (Huber, 2006;Marquis & Huston, 2003;Powell, 2000). Bower (2004) confirmed that effective and efficient designs of care management processes will be needed, guided by specific principles that include tools, roles, and outcomes in healthcare. In addition, the full immersion model defined specific caseload volumes to be managed by the RN case manager in acute care patient populations.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…(CMSA, 2005) The full immersion model of care management was built from concepts found in the case management literature related to role functions of discharge planning, utilization review, and care coordination or facilitation (Huber, 2006;Marquis & Huston, 2003;Powell, 2000). Bower (2004) confirmed that effective and efficient designs of care management processes will be needed, guided by specific principles that include tools, roles, and outcomes in healthcare. In addition, the full immersion model defined specific caseload volumes to be managed by the RN case manager in acute care patient populations.…”
Section: Introductionmentioning
confidence: 85%
“…Empiric studies of case management typically focus on clinical outcomes; specifically physiological indicators, activity and functionality levels, patient comfort, the absence of complications, and evidence of skills (Bower, 2004;Cudney, 2002;Johnson & Schubring, 1999;Lamb, 1995). Studies of the effectiveness of case management as a care delivery model have focused on the achievement of patientspecific clinical outcomes (Anthony, Brennan, O'Brien, & Suwannaroop, 2004;Cudney, 2002;Dalton, Evans, Wilson, & Roberts, 2007;Dlugacz & Stier, 2005;Lynn & Kelley, 1997;Tonges, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations